An empirical foundation for planning an emerging pedagogical method of Physical Education from the predominant learning styles - Jiménez, Víctor (Journal of Learning Styles, 2021)
The objective of this research was to make a contribution to the process of increasing knowledge through the exploratory empirical demonstration of an emerging pedagogical theory on the planning of sports training in Spain. For this purpose, a cross-sectional investigation was designed with a quantitative approach composed of a simple random sample of 120 students (n = 120) from secondary education and from the degree in Physical Activity and Sports Sciences, who were resident in Spain, and who were administered the Honey-Alonso Questionnaire (CHAEA) on learning styles (Alonso, Gallego, & Honey, 1994). The predominant learning styles were identified and the possible changes that occur in the learning styles of the students at their different educational stages were examined. The assumption of normality was calculated using the K-S test and the equality of variances using the Levene test. Student's t test was performed to compare the characteristics of both groups. The results showed the predominance of the "Reflective", "Pragmatic", "Theoretical" and "Active" styles, respectively. No significant differences were found in learning styles at stages studied. Given the importance that emerging pedagogical methods attach to individualised teaching it seems appropriate to discuss the planning of an emerging pedagogical method taking as a reference the characteristics of students based on the predominant learning styles.
Keywords: Pedagogy; Physical Education; Learning Styles; Secondary Education; Pedagogical Model